ANALISIS PERENCANAN STRUKTUR ATAS GEDUNG PERPUSTAKAAN DAN ARSIP KABUPATEN LIMA PULUH KOTA - Nentri Madona; Deddy Kurniawan (Ensiklopedia Research and Community Service Review, 2022)
Development is priority in improving quality of Human Resources. Library is one of facilities that support the development of science and information. Books are source of knowledge that make someone understand science. The goal that the author wants to achieve is to obtain the results of the Evaluation of the Library and Archives Building of Lima Puluh Kota Regency with the principle of ductility to create a building that is safe, comfortable and resistant to earthquakes. From the results of this structural analysis, the reinforcement structure is obtained from author's analysis. The results obtained that the material used is steel fy = 300 MPa and concrete quality fc' = 24.9 MPa. For reinforcement of floor slabs, reinforcement is used for the direction of x = 13 – 150, while the direction of y = 13 – 150. Column planning uses steel fy = 400 Mpa and concrete quality fc' = 24.9 MPa with a column size of 50 cm x 50 cm . While the design of the beam using steel quality fy = 300 Mpa and concrete quality fc' = 24.9 Mpa with sizes for main beam 50cm x30cm, Joist 1 45cm x25cm and joist 2 30cm x25cm.Keywords: Construction, building, ductile